Analisis Determinan Tingkat Kesempatan Kerja di Provinsi Jawa Barat - Damayanti, Laylutfi; Astuti, Ismadiyanti Purwaning (Jurnal Riset Ilmu Ekonomi, 2024)
A low level of employment opportunities cause problems in a country's economy. Low employment opportunities are caused by an increase workers number without being balanced by the availability of new jobs. This research aims to determine the effect of population, growth rate of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), and Regency/City Minimum Wage (UMK) on the level of employment opportunities in West Java Province. This research uses secondary data through quantitative methods. The analysis used is panel data regression. The research results show that population size has a positive and insignificant effect on the level of employment opportunities. The growth rate of Gross Regional Domestic Product (GRDP) and the Human Development Index (HDI) have a positive and significant effect on the level of employment opportunities, while the District/City Minimum Wage (UMK) has a negative and significant effect on the level of employment opportunities. Policy proposals for the West Java Provincial government to focus on development by developing infrastructure and investment that have the potential to create new jobs. Programs to improve the quality of human resources need to be improved to develop workforce skills. Apart from that, the government needs to consider structuring wage policies and creating decent work opportunities to protect the workforce.